Evaluation of atmospheric methane concentrations and growth trends in selected locations of Rivers State, Nigeria - Onwusameka Sonny Ogbowuokara; Tambari Gladson Leton; John Nwenearizi Ugbebor; Ochuko Felix Orikpete (The Journal of Engineering and Exact Sciences)
The study addresses the increasing atmospheric methane mixing ratios in Rivers State, Nigeria, a pressing issue linked to global warming. The objective was to analyze the growth rate and sources of methane emissions in the region. Using a quantitative approach, ground-level methane measurements were collected from seven different locations between September 2021 and June 2022, complemented by data from the Tropospheric Monitoring Instrument satellite spanning January 2019 to June 2022. The methodology combined descriptive, comparative, and regression analyses with plume chemistry modeling using the U.S. EPA Atmospheric Dispersion Modeling System software. Results indicated significant spatial variance in methane concentrations, ranging from 9.76 ppm in Ogbogu to 21.5 ppm in Choba, with notable temporal fluctuations. Regression analysis revealed a correlation between atmospheric conditions and methane levels, while plume chemistry identified a landfill near Choba market as a major emission source, raising concerns about tropospheric ozone pollution and health risks. The study highlights the need for effective waste management in Rivers State and emphasizes the importance of continuous monitoring to address the challenges posed by methane emissions and tropospheric ozone pollution.